THE FIGURATIVE LANGUAGE IN INDONESIAN PRESIDENT, MR. JOKOWI’S WORDS, AS REPORTED ON ONLINE NEWS - Abdjul, Putri Fatra; Otoluwa, Moon Hidayati; Anastasia, Happy; Mariana, Ana (Universitas Muhammadiyah Gorontalo, 2023)
The study is aimed at observing the figurative language in Mr. Jokowi's words on online news. The method used is qualitative. The technique of collecting data is through the script of the online news in The Jakarta Post and Tempo. The techniques of analyzing data are data reduction, data presentation, and conclusions drawing. The results show there are 32 data of figurative language in both news such as Simile: 1 data, Metaphor: 1 data, Personification: 4 data, Hyperbole: 1 data, Metonymy: 16 data, and Synecdoche: 9 data. The conclusions, from most of the types used by Mr. Jokowi, Metonymy, depict an attractive and personal image that he presents himself as part of the institutions that he leads. He also tries to provide and put promises as hopes and solutions to the problems that exist. The suggestions, this study hoped to provide information and as reference to the next researchers. In this study, there still is some lack, therefore it will be an opportunity for those who are interested in developing the current research, or analyzing figurative language in journalists’ words in reporting news, or even in advertisements.